Head Lice Infestation and Its Relationship with Hygiene and Knowledge among Urban School Children in Yogyakarta - Anastasia Joyce Lim Yit Zhen; E. Elsa Herdiana Murhandarwati; Sitti Rahmah Umniyati (Tropical Medicine Journal, 2011)
Introduction: Pediculosis capitis is a common infestation in school children and is a worldwide public health concern. Despite this worldwide spread, incidence studies remain few. There is also a misconceptionthat head lice infestation is rarely found in the urban environment.Objectives: The objective of this study is to determine the proportion of head lice infestation among urban school children in Yogyakarta and study its relationship with hygiene and knowledge.Methods: This is a cross-sectional study conducted upon 2 schools in Yogyakarta on 154 pupils. Children range from ages 9 to 13 years. Data was collected from the schools by trained persons. A detailed questionnaire was fi lled for each pupil prior to hair examination.Results: In this research, we report the proportion of head lice infestation among urban school children in Yogyakarta and assess its risk factors. Nineteen pupils (12.3%) were infected with head lice, 5 boys(6.3%) and 14 girls (18.7%). There was a signifi cant relationship between head lice infestation and sex (P<0.05). However, no signifi cant relationship was found between head lice infestation with hygiene andknowledgeConclusion: The results show a total proportion of 12.3% among urban school children in Yogyakarta.Keywords: pediculosis capitis, urban, hygiene, knowledge, school children.